Implications of climate change for shipping: Ports and supply chains. (8th February 2018) - Becker, Austin; Ng, Adolf K.Y.; McEvoy, Darryn; Mullett, Jane
Abstract : Ports are an important economic actor—at local, national, and international scales—that have been identified as being vulnerable to future changes to the climate. This paper details the findings from an international review of state‐of‐the‐art knowledge concerning climate risks, and adaptation responses, for ports and their supply chains. Evidence from both academic and gray literature indicates that there has already been major damage and disruption to ports across the world from climate‐related hazards and that such impacts are projected to increase in the years and decades to come. Findings indicate that while a substantial—and growing—body of scientific evidence on coastal risks and potential adaptation options is acting as a stimulus for port authorities to explicitly consider the risks for their assets and operations, only a notable few have actually made the next step toward implementing adaptation strategies. This paper concludes by putting forward constructive recommendations for the sector and suggestions for research to address remaining knowledge gaps. It emphasizes a call for collaboration between the research and practice communities, as well as the need to engage a broad range of stakeholders in the adaptation planning process. This article is categorized under: Assessing Impacts of Climate Change > Evaluating Future Impacts of Climate Change Abstract : Map showing approximately 1100 ports (green) of approximately 3700 total (red) that have come within 50 km of a tropical storm from 1960 to 2016. Storm tracks in orange (data from World Port Index and https://www.ncdc.noaa.gov/ibtracs/ ). Increase in intensity of tropical storms is one of many climate drivers expected to affect seaports and supply chains.